Consumer preferences for electric vehicles in lower tier cities of China: Evidences from south Jiangsu region. (August 2018) - Huang, Youlin; Qian, Lixian
Highlights: We investigate consumer preferences for electric vehicles in lower-tier cities of China. The key instrumental and policy attributes for EV adoption are identified. The preference heterogeneity in second-tier versus third-tier cities is compared. The effects of psychological factors on consumer preferences for EVs are examined. Government policies and business strategies should be contextualized in cities. Abstract: China is the world biggest market of electric vehicles (EVs) in terms of production and sales. Existing studies on consumer preferences for EVs in China have generally focused on first-tier cities, while little attention has been paid to the lower tier cities. This exploratory study investigates consumer preferences for EVs in lower tier cities of China, by collecting stated preference (SP) data in two second-tier cities and three third-tier cities in the south Jiangsu region of China. The discrete choice modeling analysis shows that Chinese consumers in lower-tier cities are generally sensitive to monetary attributes, charging service and driving range of EVs. They also perceive Chinese vehicle brands to be disadvantaged compared with European brands. When comparing the differences in second-tier versus third-tier cities, we find that consumers in third-tier cities are more sensitive to purchase price, subsidy of purchase, and coverage of charging stations than their second-tier counterparts. This study also highlights the role of different psychological effects, such as symbols of car ownership, normative-face influence, and risk aversion, in shaping consumer preferences for EVs in lower-tier cities of China. Our results provide important implications for contextualizing government policies and marketing strategies in line with the different sizes and characteristics of the cities in China.